Comparison of Customary Law and Islamic Law on the Tradition of Donation in Walimatul 'Urs: in Padukuhan Nepi, Kranggan Village, Galur Sub-district, Kulon Progo Regency - Rizka Mubarokati (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2024)
Marriage is a noble sunnah that has been carried out by the Prophets and Messengers and the early and late generations who followed their guidance. Walimah itself means a celebration, a banquet specifically for marriage and is not used for events outside of marriage. Walimah according to the custom in Padukuhan Nepi is very important so that to hold a walimah the community has its own way to create the event such as collecting donations with the tonjokan tradition, namely giving in the form of food or groceries given before the walimah takes place. The subject matter discussed in this thesis is how the practice of how customary law and Islamic law views the practice of giving donations walimatul 'urs? and how does the community respond to the practice of giving donations at walimatul 'urs itself? This research is a field research. Data collection techniques include observation and literature study conducted by documenting documents and literature related to the research material. This research is descriptive comparative with normative and sociological approaches. Then the analysis method used is comparative analysis to compare the two concepts and find the meeting point of the two concepts. The results of this study indicate that in understanding the practice of donations in walimatul 'urs, Islamic law provides more benefits and convenience compared to customary law. In Islamic law, giving a donation is not an obligation but a voluntary gift that is believed to be rewarded by Allah SWT, while in customary law, especially the custom in Nepi Padukuhan, giving a donation at walimatul 'urs is an obligation because if it is not implemented, it will get its own sanctions from the local community.